A brief nudge or education intervention delivered online can increase willingness to order a beef-mushroom burger. (January 2021) - Prusaczyk, Elvira; Earle, Megan; Hodson, Gordon
Highlights: A brief nudge decreased willingness to order all-beef ( vs . mushroom-beef) burger. An educational infographic also decreased willingness to order an all-beef burger. Ideology or meat-eating attitudes did not moderate effectiveness of interventions. Abstract: Increasing the consumption of plant-forward meals, such as beef-mushroom burgers, is a promising avenue for improving environmental sustainability. In the present research, we explored the effectiveness of a brief nudge or education intervention designed to reduce willingness to order an all-beef burger in favor of a beef-mushroom burger. For the nudge intervention the beef-mushroom burger was set as the default menu item, whereas for the education intervention the link between beef consumption and climate change was explained. In the control condition neither were included. Participants ( N = 562) completed measures of social dominance orientation (SDO), conservatism, cognitive rationalization of meat-eating, beef consumption, liking beef, and liking mushrooms, in a randomized order. Participants were then randomly assigned to the nudge ( n = 189), education ( n = 187), or control ( n = 186) condition, after which they reported their willingness to order an all-beef ( vs . beef-mushroom) burger. Results revealed that, after accounting for liking mushrooms, the nudge ( vs. control) condition and the education ( vs. control) condition both significantly decreased willingness to order the all-beef ( vs . beef-mushroom) burger. SDO, conservatism, cognitive rationalization of meat-eating, beef consumption, or liking beef did not moderate the effectiveness of the interventions. In other words, nudge and education interventions increased willingness to order beef-mushroom burgers regardless of right-wing ideology or meat-eating attitudes or behaviors. Implications and recommendations are discussed.